ATP6V(0)d2 controls Leishmania parasitophorous vacuole biogenesis via cholesterol homeostasis - Pessoa, Carina Carraro (PLoS Pathog, 2019)
V-ATPases are part of the membrane components of pathogen-containing vacuoles, although their function in intracellular infection remains elusive. In addition to organelle acidification, V-ATPases are alternatively implicated in membrane fusion and anti-inflammatory functions controlled by ATP6V(0)d2, the d subunit variant of the V-ATPase complex. Therefore, we evaluated the role of ATP6V(0)d2 in the biogenesis of pathogen-containing vacuoles using ATP6V(0)d2 knock-down macrophages infected with the protozoan parasite Leishmania amazonensis. These parasites survive within IFNγ/LPS-activated inflammatory macrophages, multiplying in large/fusogenic parasitophorous vacuoles (PVs) and inducing ATP6V(0)d2 upregulation. ATP6V(0)d2 knock-down decreased macrophage cholesterol levels and inhibited PV enlargement without interfering with parasite multiplication. However, parasites required ATP6V(0)d2 to resist the influx of oxidized low-density lipoprotein (ox-LDL)-derived cholesterol, which restored PV enlargement in ATP6V(0)d2 knock-down macrophages by replenishing macrophage cholesterol pools. Thus, we reveal parasite-mediated subversion of host V-ATPase function toward cholesterol retention, which is required for establishing an inflammation-resistant intracellular parasite niche.